Enhancing production effectiveness of the K-58 crankcase machining line through integrated TPM–FMEA approach - Zulkani Sinaga; Jhonni Sinaga (Jurnal Polimesin, 2025)
On the Crankcase K-58 machining line, several performance gaps were identified, including inconsistent cycle time, frequent unplanned downtime, and tool-change irregularities that caused the output to fall below the company targets. This study aims to enhance the production effectiveness of the K-58 crankcase machining line by applying an integrated Total Productive Maintenance (TPM) and Failure Mode and Effects Analysis (FMEA) approach. The initial performance evaluation, using Overall Equipment Effectiveness (OEE) in 2024, showed an average score of 76.2%, indicating significant losses in availability and performance rates. Quantitative analysis was conducted through OEE and Six Big Losses assessments, while FMEA was used to prioritize failure points based on Risk Priority Number (RPN). Improvement actions implemented included autonomous maintenance reinforcement, scheduled preventive maintenance, operator skill development, coolant-condition control, and quick-change adjustments. After implementation, OEE of the machining line increased to 85.5%, meeting the its target. Reduced speed losses improved by more than 45%, while setup and adjustment losses decreased by over 50%. These results confirm that the integrated TPM–FMEA approach is effective for enhancing machining-line performance and reliability.